Furin Functions as a Nonproteolytic Chaperone for Matrix Metalloproteinase-28: MMP-28 Propeptide Sequence Requirement - Maria Pavlaki; Stanley Zucker; Antoine Dufour; Nikki Calabrese; Wadie Bahou; Jian Cao (Biochemistry Research International)
Although MMP-28 is involved in numerous important physiologic and pathologic conditions, the mechanisms of action of this secreted proteinase is not well understood. We now have demonstrated that furin serves as an intermolecular chaperone for MMP-28 secretion by interacting with the propeptide domain of MMP-28. Employing COS-1 cells transfected with MMP-28 cDNA, protein levels of MMP-28 were quite low in conditioned media as compared to cell lysates. Coexpression of MMP-28 with furin cDNA resulted in markedly enhanced MMP-28 secretion. Contrary to expectation, cleavage of MMP-28 at the furin consensus sequence did not occur and proteolytic inactive furin was equally effective in enhancing MMP-28 secretion. Furin and MMP-28 coimmunoprecipitated and were partially coimmunolocalized in the cytoplasm of transfected cells. Cotransfection with furin cDNA also enhanced MMP-28 induced cell migration. In conclusion, our data provide a novel mechanism for MMP-28 function in cells in which furin serves as an intermolecular chaperone.